THE EFFICACY OF COMBINED BIOMARKER TESTS IN EARLY DIAGNOSTICS OF ACUTE MYOCARDIAL INFARCTION AFTER CLINICAL SYMPTOMS ONSET: ROLE OF HEART-TYPE FATTY ACID-BINDING PROTEIN - O. V. Baturina; S. R. Gilyarevsky; I. M. Kuzmina; M. A. Godkov; E. V. Klychnikova (Столичная издательская компания, 2015)
Aim. To evaluate the diagnostic value of heart-type fatty acid-binding protein (H-FABP) introduction to standard cardiac biomarkers in diagnostics of myocardial infarction (MI) early after clinical symptoms onset. Material and methods. Patients aged 18 years and older admitted to the hospital with acute coronary syndrome (ACS) during first 6 hours after ACS symptoms onset were enrolled into the study. At hospitalization level of biomarkers of myocardial damage (creatine phosphokinase-MB fraction - CPK-MB, troponin T) and qualitative tests on FABP were assessed in all patients. Serum troponin T concentration measured in 12 hours after the hospitalization was used to confirm diagnosis of MI. Moreover , diagnosis of MI was verified by echocardiography with the assessment of local reduction in myocardial contractility. Results. 101 patients were included into the study (27% female; aged 59.9±12.4). At the moment of hospitalization 71 (70%) patients were diagnosed with ACS with ST-segment elevation, and 30 (30%) patients - ACS without ST-segment elevation. In total, period between clinical symptoms onset and hospitalization was 3.6±1.4 hours. Analysis of diagnostic value of tests during the first 6 hours after ACS symptoms onset showed higher sensitivity of H-FABP in comparison with troponin T and CPK-MB (72.5, 56.2 and 49.5%, respectively). Specificity of these tests during the first 6 hours after onset of clinical signs of ACS was 90, 100 и 90%, respectively.  Sensitivity and specificity were 87.7 and 100.0%, respectively , when H-FABP , troponin T and CPK-MB were used in combination as a "block test" in patients hospitalized during the first 6 hours after ACS symptoms onset. Sensitivity and specificity were 74.3 и 100.0%, respectively , when "block test" was used in patients hospitalized during the first 3 hours after ACS symptoms onset; between 3 and 6 hours after ACS symptoms onset sensitivity and specificity of tests reached 100%. Conclusion. "Block test" with H-FABP , troponin T and CPK-MB early after ACS symptoms onset is more sensitive in comparison with separate use of the tests.